Faktor Yang Mempengaruhi Pembangunan Manusia Di Provinsi Sumatera Utara - Anisya Dwi Sukma Agsa; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to identify the factors influencing human development in North Sumatra Province. The variables examined include the poverty rate, the open unemployment rate, and economic growth across districts and cities in North Sumatra Province during the period 2017–2023. The study employs panel data analysis, with the Fixed Effect Model (FEM) selected as the most appropriate model. The results indicate that the poverty rate and economic growth have a negative and significant effect on the Human Development Index (HDI) in North Sumatra Province, while the open unemployment rate has a positive but insignificant effect on the HDI.